Defining cultural influences in Malay students' essays / YM Tengku Intan Suzila and Mohd Yusri Mohamad Noor - Tengku Sharif, YM Tengku Intan Suzila; Mohamad Noor, Mohd Yusri (Universiti Teknologi MARA Cawangan Pahang, 2003)
This paper attempts to put forward the errors made by Malay students and to analyze the errors made with relation to cultural influences. The word culture, which means "the ideas, beliefs, and customs that are shared and accepted by people in a society" (Longman Dictionary, 2001), is derived for the word "cultivate" which means, "to develop a particular skill or quality in yourself'. The question being probed is how do lecturers differentiate whether an error in a student's essay is influenced by the first language, or a result of cultural effect?